1. The problem statement, all variables and given/known data Reduce, x(w+y'+z') + (w+x)y'z + wx'yz + wxy 2. Relevant equations + stands for OR * (multiplication) stands for AND ' NOT 3. The attempt at a solution I tried to combine some terms but I cannot find a good start... x(w+y'+z') + (w+x)y'z + wx'yz + wxy = xw + xy'+ xz' + wy'z + xy'z + wx'yz + wxy I do not see what I can do. Any hint would be great. I thought maybe multiplication with one or addition of zero would help but nothing seems to work. Some rules are x+x=1 x+1=1 x+x'=1 x*x'=0 Thanks for any help.